2002
DOI: 10.1016/s0924-9338(02)80556-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial function in selected major depressive disorder patients

Abstract: 125s patients (to 37%). There are not quantitative differences in depressing reaction among patients in the beginning and ending bimonthly rehabilitation. But there are qualitative differences in manifested symptoms. The analysis of results indicates-there is a high, an adverse correlation between heightened intensity of depression and psychological needs: dominance, achievement (I=-0,64). Conclusions: 1. Rehabilitation has a strong influence on debilitation of depressive symptoms. 2. Traits of personality, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In addition, FA treatment significantly increased the gene expression levels of Hk and Pc , the rate‐limiting enzymes of the glycolysis and TCA cycle. It was previously reported that there were significant loss of mitochondrial ATP production and reduction in mitochondrial enzyme ratio in the patients with major depression . This present study shows that FA treatment increased the ATP level in the limbic area of the brain of ICR mice.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, FA treatment significantly increased the gene expression levels of Hk and Pc , the rate‐limiting enzymes of the glycolysis and TCA cycle. It was previously reported that there were significant loss of mitochondrial ATP production and reduction in mitochondrial enzyme ratio in the patients with major depression . This present study shows that FA treatment increased the ATP level in the limbic area of the brain of ICR mice.…”
Section: Discussionsupporting
confidence: 74%
“…However, MDD is increasingly viewed as an illness of the mind as well as the body (8,9). Literature already reports mitochondria-related effects in fibroblasts (1,9), muscle- (10), peripheral mononuclear blood cells (11), and platelets (12,13) of depressed patients, suggesting that mitochondria-related pathomechanisms associated with MDD can be identified and studied in neuronal and also in peripheral non-neuronal cells.…”
Section: Introductionmentioning
confidence: 99%